Analisis Platform dan Database Perangkat Lunak Sistem Informasi: Sebuah Tinjauan Literatur Sistematis - Riyandi, Krisna; Marzaq, Anas Al; Kusuma, Jordi Willyam Adi; Farisi, Ahmad (Universitas Multi Data Palembang, 2025)
This study analyzes platforms and databases in information system software development based on literature from 2022 to 2024 using the Systematic Literature Review (SLR) method. This method allows for the systematic identification of journal articles following predefined procedures. Various platforms for information system development include mobile, web, and desktop, while databases include MySQL, PostgreSQL, Firebase, MongoDB, Oracle, and SQL Server. This study aims to identify the databases used, types of developed information systems, platforms utilized, key development fields, and software development methods applied. From the 20 analyzed studies, MySQL was the most commonly used database due to its efficiency, ease of use, and high compatibility, making it the preferred choice for information system development.